Marie Curie and her daughters : the private lives of science's first family - Emling, Shelley (Palgrave Macmillan, 2012)
"Marie Curie was the first person to be honored by two Nobel Prizes and she pioneered the use of radiation therapy for cancer patients. But she was also a mother, widowed young, who raised two extraordinary daughters alone: Irene, a Nobel Prize winning chemist in her own right, who played an important role in the development of the atomic bomb, and Eve, a highly regarded humanitarian and journalist, who fought alongside the French Resistance during WWII. As a woman fighting to succeed in a male dominated profession and a Polish immigrant caught in a xenophobic society, she had to find ways to support her research. Drawing on personal interviews with Curie's descendents, as well as revelatory new archives, this is a wholly new story about Marie Curie--and a family of women inextricably connected to the dawn of nuclear physics"--